ANALISIS KEKALAHAN PETAHANA DPRD KLATEN BONDAN ZAKARIA DALAM PEMILIHAN LEGISLATIF KABUPATEN KLATEN TAHUN 2019 - Prakosa, Fandy Faisal; -, Fitriyah -; Martini, rina - (Journal of Politic and Government Studies, 2024)
The dominance of the PDI-P in Klaten Regency has caused fierce competition from the PDIP party in the 2019 election contest. This caused the phenomenon of Bondan Zakaria's defeat in the 2019 Klaten Legislative Local Election. The phenomenon of Bondan Zakaria's defeat is interesting because Bondan Zakaria's status as an incumbent was defeated by newcomers, even more so from the same party, namely from the PDIP party. Logically, as an incumbent, he has a greater chance of winning the Legislative Election than a newcomer. This study uses qualitative methods and political strategy approaches by Henry Mintzberg (1998). The findings of the problems in this study were developed using a strategic approach as a plan, pattern, position, tactic, and perspective. The results of field findings showed that Bondan Zakaria's defeat was caused by the failure of the vote acquisition target as a failure of the plan, the turmoil of the internal dynamics of Bondan Zakaria's winning team, the dispute over the opponent's tactics faced by Bondan Zakaria, and Bondan Zakaria's position and perspective as the incumbent of the Klaten DPRD that were not utilized. In this study, the author also recommends improvements in enriching arguments through various subjects as research improvements